The 2023 dengue outbreak in Lombardy, Italy: A one-health perspective - Francesca Rovida; Marino Faccini; Carla Molina Granè; Irene Cassaniti; Sabrina Senatore; Eva Rossetti; Giuditta Scardina; Manuela Piazza; Giulia Campanini; Daniele Lilleri; Stefania Paolucci; Guglielmo Ferrari; et al. (Travel Medicine and Infectious Disease)
Introduction: Here we reported the virological, entomological and epidemiological characteristics of the large autochthonous outbreak of dengue (DENV) occurred in a small village of the Lombardy region (Northern Italy) during summer 2023. Methods: After the diagnosis of the first autochthonous case on August 18, 2023, public health measures, including epidemiological investigation and vector control measures, were carried out. A serological screening for DENV antibodies detection was offered to the population. In the case of positive DENV IgM, a second sample was collected to detect DENV RNA and verify seroconversion. Entomological and epidemiological investigations were also performed. A modeling analysis was conducted to estimate the dengue generation time, transmission potential, distance of transmission, and assess diagnostic delays. Results: Overall, 416 subjects participated to the screening program and 20 were identified as DENV-1 cases (15 confirmed and 5 probable). In addition, DENV-1 infection was diagnosed in 24 symptomatic subjects referred to the local Emergency Room Department for suggestive symptoms and 1 case was identified through blood donation screening. The average generation time was estimated to be 18.3 days (95 % CI: 13.1–23.5 days). R0 was estimated at 1.31 (95 % CI: 0.76–1.98); 90 % of transmission occurred within 500m. Entomological investigations performed in 46 pools of mosquitoes revealed the presence of only one positive pool for DENV-1. Discussion: This report highlights the importance of synergic surveillance, including virological, entomological and public health measures to control the spread of arboviral infections.